IL-15 Gene Polymorphism in Celiac Disease Patients and Their Siblings - Yalçın Kara,; Makbule Eren,; Serap Arslan,; Oğuz Çilingir, (Turkish Journal of Gastroenterology, 2021)
Background: Celiac disease (CD) is an immune-mediated enteropathy characterized by lifelong gluten intolerance. Interleukin-15 (IL- 15) is a proinflammatory cytokine that is considered a key component in the immune reaction triggered by gluten. Our aim of this study was to evaluate the influence of IL-15 gene polymorphisms on CD development and clinical presentation. Methods: The study was enrolled-with 90 CD patients (49 female/41 male, median years of age 11), their 38 siblings (20 female/18 male, median years of age 8), and 99 healthy controls (66 female/33 male, median years of age 13). Their demographic findings, symptoms, and signs histopathological grade, Human Leukocyte Antigen (HLA) types were recorded. IL-15 gene polymorphisms rs2857261, rs10519613, and rs1057972 were analyzed through PCR. Results: There was a significantly higher frequency of GG genotype in rs2857972 polymorphisms and TT genotype in rs1057972 polymorphisms in celiac families compared to controls [41% vs. 23% (P = .0008), 36% vs. 11% (P = .001), respectively]. Without considering their HLA status, there was not any difference between celiacs and healthy siblings. However, when stratified according to their HLADQ2 status, rs2857972 GG polymorphism was 1.5 times prominent in celiacs than siblings at homozygous state, whereas rs1057972 TT genotype was found to be 2.5 times prominent in celiac siblings at heterozygous state. There was no association between these polymorphisms and clinical presentation. Conclusion: rs2857972 GG and rs1057972 TT variants of IL 15 are more prominent in celiac families than controls. However, the impact of IL-15 gene polymorphism on CD development is dependent on HLADQ2 status. Cite this article as: Kara Y, Eren M, Arslan S, Çilingir O. IL-15 gene polymorphism in celiac disease patients and their siblings. Turk J Gastroenterol. 2021; 32(4): 349-356.